2010
DOI: 10.1039/b920262e
|View full text |Cite
|
Sign up to set email alerts
|

Liquid phase oxidation of p-xylene to terephthalic acid at medium-high temperatures: multiple benefits of CO2-expanded liquids

Abstract: The Co/Mn/Br catalyzed oxidation of p-xylene to terephthalic acid (TPA) is demonstrated in CO 2 -expanded solvents at temperatures lower than those of the traditional Mid-Century (MC) process. As compared with the traditional air (N 2 /O 2 ) oxidation system, the reaction with CO 2 /O 2 mixture at 160• C and using an additional inert gas (N 2 or CO 2 ) pressure of 100 bar increases both the yield of TPA and the purity of solid TPA via a more efficient conversion of the intermediates, 4-carboxybenzaldehyde and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Zuo et al [3] investigated the use of CO 2 -expanded liquids (CXLs) for pX oxidation to TPA and found that the reaction with a CO 2 /O 2 mixture (with the maximum O 2 content being 50 vol%)…”
Section: Oxygen-enriched Feed Gasmentioning
confidence: 99%
See 4 more Smart Citations
“…Zuo et al [3] investigated the use of CO 2 -expanded liquids (CXLs) for pX oxidation to TPA and found that the reaction with a CO 2 /O 2 mixture (with the maximum O 2 content being 50 vol%)…”
Section: Oxygen-enriched Feed Gasmentioning
confidence: 99%
“…Figure 1.4: Structures of major impurities formed during pX oxidation to TPA Over-oxidation of hydrocarbon reactant, intermediates and solvent (also termed as "burning" [40]) along with decarboxylation and decarbonylation form the undesired products such as CO, CO 2 , water, benzoic acid, methyl acetate and methyl bromide. The formation of CO x (CO and CO 2 ) provides a measure of burning reactions and the CO 2 /CO molar ratio (the so-called "burning index") is typically around 3 [3] in the TPA process. It is estimated that 70% of acetic acid produced worldwide is used to manufacture TPA.…”
Section: Px Oxidationmentioning
confidence: 99%
See 3 more Smart Citations